First record of the genus Exilipedronia Williams, 1960 (Hemiptera: Coccomorpha: Pseudococcidae) in China, with description of a new species on bamboo - Tan, Zhixiang; Xing, Jichun (Zootaxa, 2024)
The mealybug genus Exilipedronia Williams, 1960 (Hemiptera: Coccomorpha: Pseudococcidae) is reported for the first time from Guizhou Province, China, based on a new species found infesting Bambusa sp. (Poaceae). It is described as Exilipedronia multipori Tan & Xing sp. n., and habitat photographs and illustrations are provided. The type material of E. multipori is deposited at the Institute of Entomology, Guizhou University, Guiyang, China (GUGC) and in the insect collection at the Department of Forestry Protection, Beijing Forestry University, Beijing, China (NFUC). A key to all three species of Exilipedronia is provided.